Fabrication of Hybrid Polymer Solar Cells By Inverted Structure Based on P3HT:PCBM Active Layer - Shobih Shobih; Rizky Abdillah; Erlyta Septa Rosa (LIPI Press, 2017)
Hybrid polymer solar cell has privilege than its conventional structure, where it usually has structure of (ITO/PEDOT:PSS/Active Layer/Al). In humid environment the PEDOT:PSS will absorb water and hence can easily etch the ITO. Therefore it is necessary to use an alternative method to avoid this drawback and obtain more stable polymer solar cells, namely by using hybrid polymer solar cells structure with an inverted device architecture from the conventional, by reversing the nature of charge collection. In this paper we report the results of the fabrication of inverted bulk heterojunction polymer solar cells based on P3HT:PCBM as active layer, utilizing ZnO interlayer as buffer layer between the ITO and active layer with a stacked structure of ITO/ZnO/P3HT:PCBM/PEDOT:PSS/Ag. The ZnO interlayer is formed through short route, i.e. by dissolving ZnO nanoparticles powder in chloroform-methanol solvent blend rather than by sol-gel process. Based on the measurement results on electrical characteristics of inverted polymer solar cells under 500 W/m2 illumination and AM 1.5 direct filter at room temperature, cell with annealing process of active layer at 110 °C for 10 minutes results in higher cell performance than without annealing, with an open-circuit voltage of 0.21 volt, a short-circuit current density of 1.33 mA/cm2 , a fill factor of 43.1%, and a power conversion efficiency of 0.22%. The low cell’s performance is caused by very rough surface of ZnO interlayer.